Endoscopic Management of Biliary Complications following Liver Transplantation after Donation from Cardiac Death Donors. (2012) - Croome, Kris P; McAlister, Vivian; Adams, Paul; Marotta, Paul; Wall, William; Hernandez-Alejandro, Roberto
Abstract : BACKGROUND Previous studies have shown a higher incidence of biliary complications following donation after cardiac death (DCD) liver transplantation compared with donation after brain death (DBD) liver transplantation. The endoscopic management of ischemic type biliary strictures in patients who have undergone DCD liver transplants needs to be characterized further. METHODS: A retrospective institutional review of all patients who underwent DCD liver transplant from January 2006 to September 2011 was performed. These patients were compared with all patients who underwent DBD liver transplantation in the same time period. A descriptive analysis of all DCD patients who developed biliary complications and their subsequent endoscopic management was also performed. RESULTS: Of the 36 patients who received DCD liver transplants, 25% developed biliary complications compared with 13% of patients who received DBD liver transplants (P=0.062). All DCD allograft recipients who developed biliary complications became symptomatic within three months of transplantation. Ischemic type biliary strictures in DCD allograft recipients included disseminated biliary strictures in two patients, biliary strictures of the hepatic duct bifurcation in three patients and biliary strictures of the donor common hepatic duct in three patients. CONCLUSIONS: There was a trend toward increasing incidence of total biliary complications in recipients of DCD liver allografts compared with those receiving DBD livers, and the rate of diffuse ischemic cholangiopathy was significantly higher. Focal ischemic type biliary strictures can be treated effectively in DCD liver transplant recipients with favourable results. Diffuse ischemic type biliary strictures in DCD liver transplant recipients ultimately requires retransplantation.